Devolution, Accountability, and Service Delivery in Pakistan (The Pakistan Development Review, 2010)
This paper examines into the relationship between devolution, accountability, and service delivery in Pakistan by examining the degree of accessibility of local policymakers and the level of competition in local elections, the expenditure patterns of local governments to gauge their sectoral priorities, and the extent to which local governments are focused on patronage, or providing targeted benefits to a few as opposed to providing public goods. The main findings of the paper are threefold. First, the accessibility of policy-makers to citizens in Pakistan is unequivocally greater after devolution, and local government elections are, with some notable exceptions, as competitive as national and provincial elections. Second, local government sectoral priorities are heavily tilted towards the provision of physical infrastructure—specifically, roads, water and sanitation, and rural electrification—at the expense of education and health. Third, this sectoral prioritisation is in part a dutiful response to the relatively greater citizen demands for physical infrastructure; in part a reflection of the local government electoral structure that gives primacy to village and neighbourhood-specific issues; and in part a reaction to provincial initiatives in education and health that have taken the political space away from local governments in the social sectors, thereby encouraging them to focus more towards physical infrastructure. JEL classification: H7, D72, H4 Keywords: State and Local Government, Inter-government Relations, Political Processes, Rent-seeking, Lobbying, Elections, Legislatures, and Voting Behaviour, Publically Provided Goods